Processamento sol-gel de pós bioativos vítreos e cristalinos - Siqueira, Renato Luiz (Universidade Federal de São Carlos, 2010)
In recent years, the sol-gel process has been increasingly used in the preparation of glasses and glass-ceramics with biomedical applications. Although the precursors used in this synthesis methodology are a very important parameter, few studies have investigated their influence on the synthesis of these materials. In the present work, vitreous and crystalline bioactive powders of the systems SiO2−CaO−P2O5 and SiO2−CaO−Na2O−P2O5 were synthesized by means of a sol-gel route using different phosphorus precursors. The compounds chosen were triethylphosphate (OP(OC2H5)3), phosphoric acid (H3PO4), phytic acid (C6H18O24P6), and a solution prepared by dissolving phosphorus oxide (P2O5) in ethanol. The resulting materials were characterized by differential scanning calorimetry and thermogravimetry (DSC / TG), X-ray diffraction (XRD), Fourier transform infrared spectroscopy (FTIR), scanning electron microscopy coupled with energy-dispersive spectroscopy (SEM / EDS), and by in vitro bioactivity study. The use of different precursors significantly affected the main steps of the synthesis, beginning with the gelation time. The most striking influence of these precursors in the synthesis process was observed during the thermal treatments between 700 and 1200 °C for the conversion of the gels into ceramic materials. In this case, the samples, especially those prepared using phosphoric acid, exhibited very different mineralisation behaviours, but all were proven to be bioactive with in vitro tests. The bioactivity of these materials was strongly influenced by the treatment temperature, and in the case of the crystalline materials, also by the phases present. In vitreous materials, the bioactivity decreased with the stabilisation temperature. In the crystalline materials, the in vitro bioactivity was favored by the presence of wollastonite (CaSiO3) and alpha-tricalcium phosphate (α-Ca3(PO4)2) for the system SiO2−CaO−P2O5, and by sodium calcium silicate Na2Ca2Si3O9 for the system SiO2−CaO−Na2O−P2O5.
Sol-gel processing of vitreous and crystalline bioactive powders
Keywords: Material cerâmico; Biocerâmica; Materiais bioativos; Sol-gel; ENGENHARIAS::ENGENHARIA DE MATERIAIS E METALURGICA